Transkulturasi dalam Film Indonesia: Representasi Identitas Subkultur Generasi Muda pada Film Indonesia - Euis Komalawati (Atma Jaya Indonesia Catholic University, Jakarta, 2014)
This research aims to explore how Indonesian cinema covers the transculturation in youth subculture. The research focuses on three Indonesian films, it is Virgin (Ketika Keperawanan dipertanyakan) (2004), Virgin 2: Bukan Film Porno (2009), and Virgin 3: Satu Malam Mengubah Segalanya (2011). The Vladimir Propp Narrative analysis was used to analyze how the story vs plot, the structure, and the position of the narrator. The result of this research is that the films “Virgin” provide transculturation in cultural domination from western. It looks on the structure of narration, the ideology, and the values of youth subculture.